Studi Etnobotani pada Tradisi Balimau di Kota Pariaman, Sumatera Barat - Rahmi Hulyati; - Syamsuardi; Ardinis Arbain (Jurnal Biologi Universitas Andalas, 2014)
Ethnobotany studies of Balimau tradition in Pariaman has been conducted from July to October 2012. The purpose of this study was to determine the plant species and their significance used for the Balimau tradition in Pariaman. This study was conducted using survey methods, interview, and direct plant sample collections in the field. The samples were identified at Herbarium Universitas Andalas (ANDA). The cultural significance used of plant for Balimau tradition was determined using Index of Cultural Significance (ICS). The result showed that 13 species belonging to 10 families were identified as plant species that used in Balimau tradition, namely: Cananga odorata (Annonaceae), Michelia alba (Magnoliaceae), Michelia champaca (Magnoliaceae), Jasminum sambac (Oleaceae), Pandanus amaryllifolius (Pandanaceae), Vetiveria zizanioides (Poaceae), Rosa hybrida (Rosaceae), Ixora javanica (Rubiaceae), Citrus aurantifolia (Rutaceae), Citrus hystrix (Rutaceae), Murraya paniculata (Rutaceae), Mimusops elengi (Sapotaceae), and Alpinia sp. (Zingiberaceae). Citrus aurantifolia has the highest ICS value indicated that the species was commonly used in the ritual of Balimau. Keywords : Ethnobotany, Balimau, Index of Cultural Significance (ICS)